Use of the vermilion myomucosal flap with or without the mentolabial skin flap for lower lip reconstruction Uso do retalho miomucoso do vermelhão associado ou não ao retalho cutâneo mentolabial na reconstrução do lábio inferior - Milton Paulo de Oliveira; Pedro Djacir Escobar Martins; Guilherme Larsen da Cunha; Gustavo Steffen Alvarez; Anajara Gazzalle; Evandro José Siqueira (Revista Brasileira de Cirurgia Plástica)
BACKGROUND: Several techniques that have been described for reconstructing the lower lip often produce microstomia, commissure distortion, functional impairment, and decreased sensitivity. A technique for preserving neuromuscular tissue during a single-stage lip reconstruction is reported in this study. This technique involves the use of the vermilion myomucosal advancement flap with or without the mentolabial skin flap. METHODS: This study analyzed 17 male patients with squamous cell carcinoma. The mean patient age was 54.8 years, and incidence of lip defects after resection ranged from 20% to 85%. RESULTS: Infection, nerve damage, or the requirement for surgical revision was not observed in any patient during the follow-up period of three months. Three patients had microstomia with slight posterior enlargement of the lip. All patients had good sensitivity and adequate sphincter continence. CONCLUSIONS: The use of the vermilion myomucosal flap with or without the mentolabial skin flap resulted in a minimal risk of microstomia or functional incompetence. This procedure is performed in a single surgical stage and has good aesthetic and functional results for reconstruction of up to 80% of the lower lip INTRODUÇÃO: Várias técnicas têm sido descritas para a reconstrução do lábio inferior, muitas vezes produzindo microstomia, distorção da comissura, incapacitação funcional ou diminuição da sensibilidade. Neste trabalho, é relatada uma técnica com preservação de tecido neuromuscular para reconstrução labial em um único estágio, através do uso de retalho de avanço miomucoso do vermelhão, com ou sem retalho de pele mentolabial. MÉTODO: Foram analisados 17 pacientes do sexo masculino, portadores de carcinoma de células escamosas, com média de idade de 54,8 anos, com defeitos labiais pós-ressecção de 20% a 85%. RESULTADOS: Durante um período de 3 meses de seguimento pós-operatório, nenhum paciente apresentou infecção, lesão nervosa ou necessitou de revisão cirúrgica. Três pacientes apresentaram microstomia, com alargamento discreto posterior do lábio. Todos os pacientes apresentaram boa sensibilidade e continência esfincteriana adequada. CONCLUSÕES: O uso do retalho miomucoso de vermelhão com ou sem retalho de pele mentolabial resultou em risco mínimo de microstomia ou incompetência funcional, sendo realizado em estágio cirúrgico único, além de demonstrar bons resultados estéticos e funcionais para a reconstrução de até 80% do lábio inferior